Perancangan Layanan BSI Tabungan Haji Indonesia Berbasis Mudharabah: Studi Literatur Kepatuhan Akad, Alur, dan Mitigasi Risiko - Mansiz, Ilham (Journal of Islamic Banking, Economics and Finance, 2026)
This research aims to design a BSI Hajj Savings Indonesia service based on the mudharabah contract that meets Sharia compliance standards, has an effective service flow integrated with Siskohat (Islamic system management system), and implements comprehensive risk mitigation. This research employed a systematic literature review method by reviewing OJK regulations, DSN-MUI fatwas, official BSI product documents, and academic journals related to the implementation of Sharia Hajj savings. The resulting design includes a conceptual framework for contract compliance that emphasizes the application of the profit-sharing principle, a service blueprint that maps frontstage and backstage processes in detail, and a risk and control matrix that covers operational, Sharia, liquidity, and reputation risks. This design provides strategic guidance for optimizing Sharia banking services within the Hajj ecosystem.